KEBIJAKAN SENTRALISASI BERBASIS KEARIFAN LOKAL SEBAGAI MEDIA MENINGKATKAN MUTU PENDIDIKAN DI PONDOK PESANTREN NURUL JADID - Abu Hasan Agus R; Lutfi Ghozali Usman (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
The policy of centralization based on local wisdom has an important role in improving the quality of education in accordance with local cultures, especially in educational institutions and boarding schools so that quality can be further improved, the focus of this study is to examine the policy of centralization based on local wisdom as a medium to improve the quality of education in Nurul Jadid islamic boarding school. This research is a qualitative phenomenological research by taking observational data, sampling, in depth interviews and literature view. According to the theory of the quality of educational institutions juran is to make improvements in improving the quality of education. The results of the study explained that the centralization policy was caused by three factors of leadership in the running of the centralized system:  (1) authoritative, the regulatory dimensions are very strong in the decision making process, (2) democratic, equally contributing in making decisions, (3) laissez fraire, namely releasing in making decisions. So that the centralization policy applied greatly determines the level of success in improving the quality of education.